Internet banking: Factors and levels of customers’ knowledge - Wahab, Samsudin; Badaruddin, Mohd Ishak; Bahrom, Hasan (2005)
Customers’ knowledge is the most critical factor for the success of electronic banking. Other than that, the success of the banking institution operations is also influenced by the human factors, like a sense of confidence, knowledge, security, and the strength of the banking institution.The routine activities like savings, bill settlements and credit transfers can be done in the most efficient manner nowadays compared to the old system.Most banks introduce the Internet banking system as an advantage to the customers, whereby they need not have to come to the bank premises to settle their bills.This is a relatively unexamined area of investigation that concerns customers’ knowledge towards Internet banking launched by the banking institutions.The purpose of this paper is to investigate the customers’ understanding of the term ‘internet banking’ and how they experience this service. This paper will also try to identify the factors influencing their knowledge towards Internet banking.This paper will provide suggestions to the banking institutions on how to implement this Internet banking in the most efficient way in term of gaining the high quality Internet banking services.This research was carried out qualitatively.Selected customers from the various government departments were interviewed and their responses were recorded, transcribed, interpreted, and analysed based on the theme(s) of the research. Data were collected through an in-depth, open-ended interview method. The criteria for selecting the participants are their educations, occupations, ages, and their gender. Participants were 10 government officers in the various departments in Dungun, Terengganu.This research found that generally most of the participants understand the concept of internet banking. The sources of their knowledge are from banks, work experiences, friends, readings, and promotional activities through advertisements.Most of them have experiences of using IB for bill payment, Inter-bank Fund Transfer, Loan Payment, Balance Enquiry, credit card payment and also checking the summary of payments.